Fatigue in U12 soccer-7 players during repeated 1-day tournament games—a pilot study - Sanchez-Sanchez, J.; Sanchez, M.; Hernandez, D.; Ramirez-Campillo, R.; Martinez, C.; Nakamura, Y. F. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to describe and compare the distances and displacement speeds of U12 Soccer-7 athletes during 4 tournament Soccer-7 games (TG) played in less than 24 hours (experimental condition) with those recorded during 2 league Soccer-7 games (LG) with 24 hours of rest before the match (control condition). Ten participants (age = 10.3 ± 0.5 years) were recruited for the study. Main data analyzed during games included distance completed relative to match duration (Drel), maximal velocity, and distance completed at different running speeds (including acceleration, deceleration, standing, walking, jogging, medium-intensity running, high-intensity running, and sprinting). For data collection during games, athletes wore a global positioning system unit. Different (p = 0.05) mean playing time was recorded during TG and LG (15.1 and 31.8 minutes/match, respectively). Drel during the 4 TG was maintained between 85.7 ± 8.5 and 87.5 ± 8.5 m·min-1 (p > 0.05) and during the 2 LG between 84.2 ± 10.9 and 87.5 ± 9.9 m·min-1 (p > 0.05). Moreover, similar Drel was recorded during TG and LG (86.8 and 85.9 m·min-1, respectively). Compared with LG, during TG, maximal velocity was lower (23.0 and 21.3 km·h-1, respectively; p = 0.05). In addition, compared with the last game of the tournament, in the preceding games, the distance covered at low speeds (3.1-8.0 km·h-1) was lower (37.7 and 32.4%, respectively; p = 0.05) and at high speeds (=18.1 km·h-1) tends to be higher (2.5 and 3.3%, respectively). Therefore, compared with the control condition, accumulated Soccer-7 games with less than 24 hours of interday rest negatively affect displacement speed distribution (but not overall relative distances) in U12 Soccer-7 athletes. These results may help to better plan training and competition schedules to youth players